Effect of Sodium Supplements and Climate on Dysnatremia During Ultramarathon Running. Issue 6 (November 2021) - Lipman, Grant S.; Burns, Patrick; Phillips, Caleb; Jensen, Jacob; Little, Colin; Jurkiewicz, Carrie; Jarrett, Bryan; Walker, Anne; Mansfield, Nicky; Krabak, Brian J.
Abstract : Objective: Analyze the effect of sodium supplementation, hydration, and climate on dysnatremia in ultramarathon runners. Design: Prospective observational study. Setting: The 2017 80 km (50 mile) stage of the 250 km (150 mile) 6-stage RacingThePlanet ultramarathon in 2017 Chilean, Patagonian, and 2018 Namibian, Mongolian, and Chilean deserts. Participants: All race entrants who could understand English were invited to participate, with 266 runners enrolled, mean age of 43 years (± 9), 61 (36%) females, average weight 74 kg (± 12.5), and average race time 14.5 (± 4.1) hours. Post-race sodium collected on 174 (74%) and 164 (62%) participants with both the blood sample and post-race questionnaire. Intervention: Weight change and finish line serum sodium levels were gathered. Main outcome measures: Incidence of exercise-associated hyponatremia (EAH; <135 mmol·L −1 ) and hypernatremia (>145 mmol·L −1 ) by sodium ingestion and climate. Results: Eleven (6.3%) runners developed EAH, and 30 (17.2%) developed hypernatremia. Those with EAH were 14 kg heavier at baseline, had significantly less training distances, and averaged 5 to 6 hours longer to cover 50 miles (80 km) than the other participants. Neither rate nor total ingested supplemental sodium was correlated with dysnatremia, without significant differences in drinking behaviors or type of supplement compared with normonatremic runners. Hypernatremic runners were more often dehydrated [8 (28%), −4.7 kg (± 9.8)] than EAH [4 (14%), −1.1 kg (± 3.8)] ( P < 0.01), and EAH runners were more frequently overhydrated (6, 67%) than hypernatremia (1, 11%) ( P < 0.01). In the 98 (56%) runners from hot races, there was EAH OR = 3.5 [95% confidence interval (CI), 0.9-25.9] and hypernatremia OR = 8.8 (95% CI, 2.9-39.5) compared with cold races. Conclusions: This was the first study to show that hot race climates are an independent risk factor for EAH and hypernatremia. Sodium supplementation did not prevent EAH nor cause hypernatremia. Longer training distances, lower body mass, and avoidance of overhydration were shown to be the most important factors to prevent EAH and avoidance of dehydration to prevent hypernatremia.